1977
DOI: 10.1007/bf01842078
|View full text |Cite
|
Sign up to set email alerts
|

II. Extra-auditory effects in short-term exposure to aircraft and traffic noise

Abstract: Summary A series of human studies was performed in 12 young healthy male subjects to investigate extra-auditory effects of short-term ( 15 min) exposure to aircraft noise ( 84-91 d B(A)), to traffic noise (Leq 83 5 d B(A)), to mental load, and to combined load (noise + mental load) Exposure to noise caused increase of diastolic blood pressure and respiratory rate, decrease of pulse pressure and quotient of heart rate/respiratory rate and also decrease of performance in a mental task Aircarft and traffic noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 11 publications
1
5
0
2
Order By: Relevance
“…Chronic stress including noise has been found to accelerate the development of structural vascular changes in the precapillary resistance vessels and also hypertension in animals (26). This and other studies have shown that shorttime exposure to noise causes a temporary increase in blood pressure (15)(16)(17)(18)(19)(20). Repeated exposure to noise could then explain the increased prevalence of hypertension observed in humans exposed to severe noise for many years (5-8).…”
Section: -822991mentioning
confidence: 59%
“…Chronic stress including noise has been found to accelerate the development of structural vascular changes in the precapillary resistance vessels and also hypertension in animals (26). This and other studies have shown that shorttime exposure to noise causes a temporary increase in blood pressure (15)(16)(17)(18)(19)(20). Repeated exposure to noise could then explain the increased prevalence of hypertension observed in humans exposed to severe noise for many years (5-8).…”
Section: -822991mentioning
confidence: 59%
“…Since stress causes vigilance and alerted attention (Liston et al 2009), it is not unlikely that persons who perceive stress also may respond with alertness to sound. The other way around, thus sensitivity to sound increasing sensitivity to stress, is also be possibly, since unwanted sounds by definition are classified as noise, and noise is a strong stressor (Carter and Beh 1989; Mosskov and Ettema 1977). …”
Section: Introductionmentioning
confidence: 99%
“…We found some different effects of exposure to noise. For example, no influence or even a decrease of the systolic blood pressure was found in our laboratory (Mosskov et al 1977), an increase…”
Section: Confounding Factors and Conflicting Resultsmentioning
confidence: 59%